The escape room [compact disc, unabridged] - Goldin, Megan (Macmillan Audio, 2019)
In the lucrative world of Wall Street finance, Vincent, Jules, Sylvie and Sam are the ultimate high-flyers. Ruthlessly ambitious, they make billion-dollar deals and live lives of outrageous luxury. Getting rich is all that matters, and they'll do anything to get ahead. When the four of them are ordered to participate in a corporate team-building exercise that requires them to escape from a locked elevator, things start to go horribly wrong. They have to put aside their fierce office rivalries and work together to solve the clues that will release them. But in the confines of the elevator, the dark secrets of their team are laid bare. They are made to answer for profiting from a workplace where deception and intimidation thrive.